Quantum effect-based flexible and transparent pressure sensors with ultrahigh sensitivity and sensing density - Lan Shi (Nature Portfolio, 2020)
Though flexible pressure sensors with high sensitivity are attractive for health monitoring applications, existing device sensing mechanisms limit their practical applicability. Here, the authors report quantum tunnelling-based pressure sensors with high sensitivity and fast signal readout.